Success rate in preterm uterine contraction inhibition with tocolytic agents in a tertiary care center - Kiatsuda D; Thinkhamrop J; Prasertcharoensuk W (Dove Medical Press, 2016)
Duangsamorn Kiatsuda, Jadsada Thinkhamrop, Witoon Prasertcharoensuk Department of Obstetrics and Gynecology, Faculty of Medicine, Khon Kaen University, Khon Kaen, Thailand Objective: This study aims to assess the success rate of inhibiting preterm uterine contraction with tocolytic agents to delay delivery for at least 48 hours and risk factors of failure inhibition.Materials and methods: Between January 2013 and July 2014, medical records of all singleton pregnant women between 24 0/7 and 33 6/7 weeks of gestation with the diagnosis of preterm labor (with cervical dilatation) or threatened preterm labor (without cervical dilatation) who received tocolytic agents were reviewed. The success rate of preterm uterine contraction inhibition was accounted in patients with 48 hours delayed delivery. The risk factors of the inhibition failure and neonatal outcomes were also investigated in this study.Results: Among 424 pregnant women diagnosed of preterm labor or threatened preterm labor, 103 singleton pregnant women met the study criteria. Overall success rate of preterm uterine contraction inhibition to prolong pregnancy for at least 48 hours was 86.4% (95% confidence interval [CI]: 78.3, 92.3). However, the success rate among the threatened preterm labor group was 93.8% (95% CI: 88.3, 99.1) while the preterm labor group was 60.9% (95% CI: 39.3, 82.4). The significant factor associated with inhibition failure was preterm labor (adjusted odds ratio 7.22; 95% CI: 1.99, 26.20).Conclusion: The success rate of preterm uterine contraction inhibition with tocolytic agents to delay delivery for at least 48 hours was high in threatened preterm labor and low in preterm labor. A significant risk factor for inhibition failure was the preterm uterine contraction with cervical change. Keywords: inhibition of uterine contraction, success rate, preterm labor, threatened preterm labor, tocolytic agents